Bioefficacy of dietary chromium picolinate and chromium yeast on growth performance and blood biochemical in Red Tilapia, Oreochromis niloticus (Linnaeus). (19th October 2017) - Rakhmawati, Rakhmawati; Suprayudi, Muhammad Agus; Setiawati, Mia; Widanarni, Widanarni; Junior, Muhammad Zairin; Jusadi, Dedi
Abstract: This study was conducted to evaluate bioefficacy of dietary chromium picolinate and chromium yeast on growth performance and blood biochemical in red tilapia, Oreochromis niloticus (Linnaeus). Seven isonitrogenous and isocaloric experimental feeds were prepared (approximately 29% and 3, 900 kcal/kg). These diets were supplemented with different sources and levels of dietary chromium: 0.5, 1, 2 and 4 mg/kg of Cr picolinate and 2 and 4 mg/kg of Cr yeast and one control group, all groups were arranged triplicate. After a 60‐day feeding experiment, specific growth rate (SGR), feed efficiency ratio (FER) and feed utilization were observed. Blood biochemistry consisted of serum total protein, glucose, insulin, cholesterol, triglycerides, high‐density lipoprotein (HDL) and low‐density lipoprotein (LDL) were measured. Chromium distribution in several organs and glucose tolerant test were measured. The result shows that CrPic of 1 mg/kg and CrYst of 2 mg/kg produced the best SGR (2.91 ± 0.03% and 2.91 ± 0.04%), improved insulin sensitivity (7.30 ± 2.96 and 1.70 ± 0.78 μIU/ml) and increased glucose utilization. CrYst supplementation of 2 mg/kg feed resulted in the highest FER (0.79 ± 0.01) and the lowest triglycerides (126.24 ± 12.36 mg/dl). In conclusion, dietary chromium picolinate at 1 mg/kg or chromium yeast at 2 mg/kg significantly improved bioefficacy on growth performance and blood biochemicals in red tilapia.